2021
DOI: 10.1186/s13567-021-00917-x
|View full text |Cite
|
Sign up to set email alerts
|

CrfP, a fratricide protein, contributes to natural transformation in Streptococcus suis

Abstract: Streptococcussuis (S.suis) is an important zoonotic pathogen that causes septicaemia, meningitis and streptococcal toxic shock-like syndrome in its host, and recent studies have shown that S.suis could be competent for natural genetic transformation. Transformation is an important mechanism for the horizontal transfer of DNA, but some elements that affect the transformation process need to be further explored. Upon entering the competent state, Streptococcus species stimulate the transcription of competence-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…One study found that deletion of CbpD reduced transformation efficiency in Streptococcus thermophilus 42 . The same has been observed in Streptococcus sanguinis lacking LytF 43 and Streptococcus suis , lacking CrfP 44 , which are both functional analogues of CbpD.…”
Section: Discussionsupporting
confidence: 66%
“…One study found that deletion of CbpD reduced transformation efficiency in Streptococcus thermophilus 42 . The same has been observed in Streptococcus sanguinis lacking LytF 43 and Streptococcus suis , lacking CrfP 44 , which are both functional analogues of CbpD.…”
Section: Discussionsupporting
confidence: 66%
“…After entry into the cells, foreign DNA is taken over by DNA-binding proteins and the homologous recombination system. A fratricidal protein called CrfP regulated by ComR and ComX has been described recently in S. suis [ 70 ]. This protein is an exported murein hydrolase composed of one N-terminal CHAP domain capable of lysing the target cell and two SH3b domains capable of recognizing and binding the cell wall of S. suis .…”
Section: Dissemination Of Amr Genes Through Horizontal Gene Transfer In S Suismentioning
confidence: 99%
“…This protein is an exported murein hydrolase composed of one N-terminal CHAP domain capable of lysing the target cell and two SH3b domains capable of recognizing and binding the cell wall of S. suis . Inactivation of this protein reduced the transformation rate [ 70 ]. The biological function of CrfP is likely to lyse and release DNA from related Streptococcus strains to provide homologous DNA to competent recipient cells.…”
Section: Dissemination Of Amr Genes Through Horizontal Gene Transfer In S Suismentioning
confidence: 99%
“…While our current study was focused on Spn , we hypothesize that other bacteria may employ similar bet-hedging strategies during infection. It is now increasingly appreciated that various bacterial species routinely employ intra- and inter-strain predation to perpetuate their own survival (Arenas et al, 2015; Bushin et al, 2020; González-Pastor et al, 2003; Jamet et al, 2015; Zhu et al, 2021). Both quorum sensing and bacteriocin production are behaviors commonly exhibited by microbes.…”
Section: Discussionmentioning
confidence: 99%